Preliminary study on Cyclocodon lancifolius leaf blight and screening of Bacillus subtilis as a biocontrol agent - Yang, Xin; Dang, You-chao; Chen, Jing-zhong; Xu, Ke-cheng; Dai, Dao-die; Sun, Qing-wen (Frontiers in Microbiology, 2024)
This study aimed to identify the pathogen responsible for leaf blight in Cyclocodon lancifolius, investigate its biological characteristics, and identify effective synthetic fungicides. Additionally, this study examined changes in physiological and biochemical indices of leaves following pathogen infection and screened biocontrol bacteria that inhibit the pathogen growth, providing a scientific basis for preventing and managing leaf blight in C. lancifolius. Pathogens were isolated from the interface of healthy and infected leaf tissues and identified through morphological and molecular biological methods. Amplification and sequencing of three genomic DNA regions-internal transcribed spacer region, translation elongation factor 1-α, and glyceraldehyde-3-phosphate dehydrogenase of ribosomal DNA-were performed, followed by the construction of a phylogenetic tree. The biological characteristics of pathogens under various temperature and pH conditions and different nitrogen and carbon sources were analyzed using the mycelial growth rate method. The antifungal effects of 13 chemical agents were evaluated using the poisoned medium method and mycelial growth rate method. Changes in physiological and biochemical indicators post-infection were also assessed. An antagonistic experiment was conducted to screen for biocontrol bacteria. A total of 29 potential pathogenic strains were isolated from infected leaf tissues, with Koch's Postulates confirming Stemphylium lycopersici as a key pathogen causing the disease. Growth analysis of S. lycopersici revealed optimal growth at 20°C and pH 6, with lactose or maltose serving as the most suitable carbon source and histidine as the preferred nitrogen source. Among the 13 synthetic fungicides tested, strain DHY4 exhibited the greatest sensitivity to 400 g/L flusilazole.Significant differences (p < 0.05) were observed in superoxide dismutase, phenylalanine ammonia-lyase, peroxidase, polyphenol oxidase, catalase, and malondialdehyde levels between treated and control groups 3 days post-inoculation.The biocontrol strain DYHS2, identified as a strain of Bacillus subtilis, demonstrated an inhibition rate of 51.80% against S. lycopersici in dual-culture experiments and showed a relative inhibition rate of 78.82% in detached leaf assays. These findings provide valuable insights into the newly identified causal agent of leaf blight in C. lancifolius and its biological characteristics, underscoring the potential of B. subtilis DYHS2 and synthetic fungicides such as flusilazole as effective disease management strategies.